GUARANTEEING CUSTOMER SATISFACTION THROUGH ENHANCED PACKAGING DESIGN FOR POTATO CHIPS: A QFD ANALYSIS - 1M. B. Hossain, T. Wicaksono; Illés, C. B. (International Journal of Political Science and International Relations (IJPSIR), 2022)
Packaging plays a crucial role in maintaining brand equity and promoting sales by protecting goods and food items from external factors. The primary functions of packaging include safeguarding products during transportation and serving as a convenient container for consumers. In the realm of food and beverage packaging, it is not merely a wrapper; rather, it is responsible for ensuring the safety and quality integrity of the packaged products. This research focuses on the improvement of cassava chip packaging, which has been marred by several issues, such as inappropriate sizes and susceptibility to breakage, leading to customer dissatisfaction.To address these packaging challenges and enhance market competitiveness, this study employs the Quality Function Deployment (QFD) method, aiming to involve customers in the packaging design improvement process to ensure customer satisfaction. The application of the QFD method enables the formulation of recommendations for packaging design enhancements. These recommendations encompass the utilization of attractive colors, waterproof materials, and easy-to-open and close packaging covers, convenient distribution sizes, inclusion of producer information, and utilization of legible fonts. Cassava chips with chili sauce are gaining popularity in Indonesia, particularly in the city of Lhokseumawe, where home industries engage in their production. However, the packaging used in these industries often lacks attractiveness and innovation, limiting the product's market expansion. Moreover, incomplete product information on the packaging diminishes its appeal to buyers and hampers its competitiveness against rival products. As a result, the study's focus on enhancing packaging design aims to communicate the personality and unique function of the consumer product, ultimately acting as a marketing tool.For micro, small, and medium enterprises (MSMEs), particularly those involved in food and beverage processing, packaging design becomes a pivotal aspect of their overall product development process. The findings from this research contribute to improving packaging standards, addressing customer needs, and enhancing product quality, thus bolstering the competitiveness of MSMEs in the food and beverage sector.